Interface definition language and object request broker for integration of distributed heterogeneous bioinformatics software - Zuraini Ali Shah, 1974-; Shahreen Kasim; Muhamad Razib Othman; Safa'ai Deris, 1955-; International Conference on Computer Graphics and Multimedia (2nd : 2004 : Bangi, Selangor) (Skudai : Universiti Teknologi Malaysia, 2004)
57